Odpowiedzi

2010-03-21T17:04:53+01:00
A)(a+2)h dla a=7 i h=1/3
(7+2)1/3=9*1/3=3


b)4x y(x+y) dla x=6 i y=-2

4*6*(-2)*(6-2)=-48*4=-192

c)-x+2y-3 dla x=-5 i y=-4

5+2*(-4)-3= -6
3 4 3
2010-03-21T17:04:58+01:00
A)(a+2)h dla a=7 i h=1/3
(7+2)*1/3=9*1/3=3

b)4x y(x+y) dla x=6 i y=-2
4*6*-2(6-2)=-48*4=-192

c)-x+2y-3 dla x=-5 i y=-4
5-8-3=-6
21 5 21
2010-03-21T17:09:47+01:00
A) (a+2)*h
(7+2)* 1/3
9*1/3 = 3

b)4x y(x+y)
4*6*(-2)(6+(-2))
24*(-2)*4
24*(-8) = -192

c)-x+2y-3
5+2*(-4)-3
5+(-8)-3 = -6
33 4 33